2000
DOI: 10.1161/01.cir.102.16.1879
|View full text |Cite
|
Sign up to set email alerts
|

First Human Experience With Pulmonary Vein Isolation Using a Through-the-Balloon Circumferential Ultrasound Ablation System for Recurrent Atrial Fibrillation

Abstract: Background-Standard mapping and ablation of focal sources of atrial fibrillation are associated with very long procedure times and low efficacy. An anatomic approach to complete pulmonary vein isolation could overcome these limitations. Methods and Results-Fifteen patients with atrial fibrillation refractory to medication underwent circumferential isolation of the pulmonary veins by using a novel catheter, with an ultrasound transducer (8-MHz) mounted near the tip, in a saline-filled balloon. Twelve atrial foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
153
0
5

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(158 citation statements)
references
References 4 publications
0
153
0
5
Order By: Relevance
“…Alternatively, different energy sources have been used for circumferential ablation through radial energy delivery. Natale et al 7 reported the use of ultrasound balloon catheter to isolate PV from the left atrium, which was accomplished in 60% 7 . In the present study, PV isolation was achieved in 64% after mean energy delivery duration of 280 ± 177 sec, which is very similar to that reported by Natale et al 7 However, our rates of PV isolation increased to 79% when no blood flow leaks were observed.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, different energy sources have been used for circumferential ablation through radial energy delivery. Natale et al 7 reported the use of ultrasound balloon catheter to isolate PV from the left atrium, which was accomplished in 60% 7 . In the present study, PV isolation was achieved in 64% after mean energy delivery duration of 280 ± 177 sec, which is very similar to that reported by Natale et al 7 However, our rates of PV isolation increased to 79% when no blood flow leaks were observed.…”
Section: Original Articlementioning
confidence: 99%
“…In order to decrease recurrence of AF and avoid PV stenosis, PV isolation has been proposed as the endpoint for ablation, either with RF or alternative energy such as ultrasound and laser [7][8][9] . A novel laser balloon catheter ablation (LBCA) strategy was recently developed to electrically isolate the PV from the left atrium by creating circumferential lesions at the PV ostium 10 .…”
Section: Introductionmentioning
confidence: 99%
“…18 Although electrical isolation also can be achieved by circumferential ablation of the entire ostium, 19 segmental ostial ablation targets only the ostial sites at which electrical connections are present, which often is 50-60% of the entire ostial circumference. 13,17 Therefore, segmental ostial ablation avoids unnecessary injury to the pulmonary veins.…”
Section: Segmental Ostial Ablationmentioning
confidence: 99%
“…18 To overcome these limitations, researchers have recently developed a novel catheter ablation approach that involves circumferential lesions created around the ostia of each PV, with the aim of isolating these veins electrically from the left atrium while reducing the risk of PV stenosis. 31,32 This approach eliminates the need for mapping, while it also has the advantage of being able to deal with multiple foci in the PVs, which possibly would not all have been mapped or ablated if the focal ablation approach had been employed.…”
Section: Circumferential Ablationmentioning
confidence: 99%
“…Instead of delivering multiple, contiguous point applications of RF energy in a circumferential fashion as carried out by Pappone et al, the circumferential ablation approach has recently been tested using ultrasound energy delivered through a balloon in the pulmonary vein by Natale et al 32 In their recent study of 15 patients refractory to medication, a novel catheter (Atrionix catheter system, Atrionix, Palo Alto, Calif., USA), with an ultrasound transducer (8 MHz) mounted near the tip, in a saline-filled balloon, was used to produce circumferential isolation of the pulmonary veins. The safety of this technique was supported by their preliminary results showing no evidence of narrowing when assessed by repeat venography or follow-up computed tomography scan.…”
Section: Circumferential Ablationmentioning
confidence: 99%